Evaluative study algorithm for wireless Handover using Fuzzy Logic - Ronald Percing Coaguila Gómez (2019)
This research aims to analyze the Mobile HANDOVER algorithm evaluating thecharacteristics of the main models. This alternative system is exposed to the problem of applying the HANDOVER Control multicobertura Fuzzy Logic and sets a precedent for continued research on Fuzzy Control applied to Telecommunications. The analysis begins by describing the concept of HANDOVER, then examines the principle of Fuzzy Logic algorithms related mentioning some control of the propagation of the beams of radiation elements Cellular Base Station involved. The evaluation process HANDOVER algorithm is a logical proposal, which aims to improve the decrease in call transfer when applied in similar settings in Mobile Communications 2.75G, 3G, next generation Mesh Networks or 802,21 Networks. The results confirm the decrease with the resulting benefits of reduced system resources.